Plasma proteomic signature of neonates in the context of placental histological chorioamnionitis - Jing Liu; Qi Sun; Qi Zhang; Fang Ye; Yuanmei Chen; Lijuan Tang; Die Liu; Yunchao Su; Haixiao Liang (BMJ Publishing Group, 2024)
Background Placental histological chorioamnionitis (HCA) is recognised as a significant risk factor for various adverse neonatal outcomes. This study aims to explore if the inflammatory protein levels in neonates were associated with HCA.Methods All women with singleton births from February 2020 to November 2022 were selected and divided into three groups based on maternal placental pathology results: the HCA-stage 1 group (n=24), the HCA-stage 2 group (n=16) and the control group (n=17). Olink Target 96 Inflammation Panel was used to detect the levels of 92 inflammation-related proteins in the plasma of newborns from all three groups within 24 hours after birth. We compared the protein profiles through differential protein expression analysis.Results A total of six inflammation-related proteins exhibited significant differences between the HCA-stage 1 and the control group. Specifically, TRANCE and CST5 were significantly upregulated (p=0.006, p=0.025, respectively), whereas the expression of IFN-gamma, CXCL9, CXCL10 and CCL19 was significantly downregulated (p=0.040, p=0.046, p=0.007, p=0.006, respectively). HCA-stage 2 newborns had significantly elevated levels of CD5 and CD6 and decreased IFN-gamma, CXCL10 and CCL19 in comparison to controls. These differential proteins were significantly enriched in positive regulation of cytokine activity, leucocyte chemotaxis and positive regulation of T-cell activation pathway-related Gene Ontology terms. Kyoto Encyclopedia of Genes and Genomes pathway analysis revealed that viral protein interaction with cytokine and cytokine receptor, interleukin-17/NF-kappa B/toll-like receptor/chemokine signalling pathway, and cytokine-cytokine receptor interaction exhibited significant differences. Spearman analysis demonstrated a significant positive connection between the levels of CD6 and CD5 proteins, not only in neonatal leucocytes but also in maternal leucocytes. Additionally, CD6 was found to be associated with neonatal birth weight.Conclusions In conclusion, placental histological changes associated with chorioamnionitis appear to influence the expression of inflammatory proteins in offspring. Notably, CD6 and CD5 proteins may potentially contribute to the pathogenesis of HCA-related neonatal diseases.